Bus seat suspension modification for pregnant women - Mohammad, Gohari; Roslan, Abdul Rahman, Dr.; Raja Ishak, Raja Hamzah, Dr.; Mona, Tahmasebi (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/